Politics of Inclusion and Adaptive Physical Education: A Systematic Review of Policy Implementation for Students with Special Needs - Anwar, Choirul; Rozi, Fatkhur; Binti Hasan, Siti Nursyahiirah (Austronesia Akademika, 2025)
Inclusive adaptive physical education has emerged as a critical focus within global educational policy, particularly in advancing equitable access for students with special needs. This study aims to synthesize current knowledge on the politics and implementation of inclusive adaptive physical education policies from 2020 to 2025. Using a systematic literature review approach guided by the PRISMA 2020 protocol, 53 peer-reviewed articles were analyzed through mixed methods, combining bibliometric mapping with thematic content analysis. Results reveal a sharp increase in publications peaking in 2022, influenced by global equity movements and the COVID-19 pandemic, followed by a decline suggesting research fatigue or a shift toward practice-oriented studies. Conceptually, the literature is dominated by traditional paradigms such as Universal Design for Learning and the social model of disability, which prioritize curriculum flexibility, teacher training, and access to physical activity. However, gaps remain in addressing emerging dimensions like intersectionality, cultural responsiveness, and institutional reform. The findings also highlight that implementation is frequently educator-centric, potentially neglecting broader structural and community-based factors. This study contributes to the existing knowledge base by offering a synthesized framework that integrates global policy, conceptual foundations, and practical mechanisms, while also identifying the limitations of current approaches. The results underscore the need for more context-sensitive, inclusive, and collaborative policy designs. Future research should engage in longitudinal and cross-cultural inquiries, incorporate diverse stakeholder voices, and build international networks to ensure the sustainability and impact of inclusive adaptive physical education practices.